Effects of ageing on the anterior segment of the eye structure and function - Cerviño, Alejandro (2018)
[Excerpt] The world will soon have more aged people than children and more people at extreme old age than ever before [1]. Improving quality of life as well as reducing severe disability due to age-related problems has become key for the health systems worldwide. The ageing of the world population has both structural and functional consequences for the human visual system; changes due to ageing occur in all the structures of the eye causing a variety of eﬀects. Over the last few years, great advances in ophthalmic instrumentation allow the determination of ocular parameters to a level of detail without precedent. Such advances allowresearcherstodevelopspeciﬁcdevicesforvisualcorrection and rehabilitation and at the same time guide the clinicians in their decision making and selection of treatment options to convey with the increasing demand of highquality outcomes of the ageing population. This special issue aimed at creating a multidisciplinary forum of discussion on recent advances in the knowledge of the eﬀects of ageing in the anterior segment of the human eye’s structure and function, and improvements on early detection, treatment, and prognosis of age-related ocular conditions of the anterior segment. As a result, a remarkable compilation of ten articles cover many of these very diﬀerent aspects of ocular ageing. [...]